Association Between ERCC1 rs3212986 and ERCC2/XPD rs1799793 and OS in Patients With Advanced Esophageal Cancer - Boldrin, Elisa; Malacrida, Sandro; Rumiato, Enrica; Battaglia, Giorgio; Ruol, Alberto; Amadori, Alberto; Saggioro, Daniela (Frontiers in Oncology, 2019)
Esophageal cancer (EC) is a very aggressive tumor, and no reliable prognostic markers exist especially for resectable advanced neoplasia. The principal aim of this study was to investigate the association of germline polymorphisms in nucleotide excision repair (NER) pathway genes with the overall survival (OS) of patients with advanced EC. As a second aim, we also studied the association of NER gene variants with response to cisplatin-based chemotherapy. Among the EC patients referred to our Institution between 2004 and 2012, we selected a cohort of 180 patients diagnosed with a clinical tumor stage ranging from IIB and IVA. Patients were genotyped for four NER variants, two in the ERCC1 (rs11615 and rs3212986) and two in the ERCC2/XPD (rs1799793 and rs13181) genes. Kaplan–Meier analyses and Cox proportional hazards model were used to evaluate the associations of the selected variants with OS; association with response to neoadjuvant therapy was investigated using logistic regression. Results showed that the ERCC1 rs3212986 and the ERCC2/XPD rs1799793 were significantly associated with shorter OS. On the contrary, response association analysis displayed that, while rs11615 and rs3212986 in ERCC1 were associated with response, both ERCC2/XPD variants were not. By creating survival prediction models, we showed that the rs3212986 and the rs1799793 have a better predictability of the tumor stage alone. Furthermore, they were able to improve the power of the clinical model (AUC = 0.660 vs AUC = 0.548, p = 0.004). In conclusion, our results indicate that the ERCC1 rs3212986 and the ERCC2/XPD rs1799793 could be used as surrogate markers for a better stratification of EC patients with advanced resectable tumor.